Dual‐Metal Electrolytes for Hybrid‐Ion Batteries: Synergism or Antagonism?. Issue 11 (5th May 2021) - Rasheev, Hristo; Stoyanova, Radostina; Tadjer, Alia
Abstract: The construction of hybrid metal‐ion batteries faces a plethora of challenges. A critical one is to unveil the solvation/desolvation processes at the molecular level in electrolytes that ensure efficient transfer of several types of charge carriers. This study reports first results on simulations of mixed‐ion electrolytes. All combinations of homo‐ and hetero‐binuclear complexes of Li +, Na + and Mg 2+, solvated with varying number of ethylene carbonate (EC) molecules are modeled in non‐polar and polar environment by means of first principles calculations and compared to the mononuclear analogues in terms of stability, spatial organization, charge distribution and solvation/desolvation behavior. The used PF6 − counterion is shown to have minor impact on the geometry of the complexes. The desolvation energy penalty of binuclear complexes can be lowered by the fluoride ions, emerging upon the PF6 − decay. These model investigations could be extended to rationalize the solvation structure and ionic mobility in dual‐ion electrolytes. Abstract : Dual‐metal electrolytes allow converting hybrid‐ion batteries into competitors of the lithium‐ion ones. Instead of shuttling one ion, these electrolytes ensure the transport of two types of cations. Applying DFT calculations, the synergistic and antagonistic interactions upon solvation/desolvation of cationic pairs of Li +, Na + and Mg 2+ with ethylene carbonate are simulated.